Modelling and performance analysis of energy detector-based spectrum sensing with maximum ratio combining over Nakagami-m/log-normal fading channels. (2nd July 2019) - Verma, Pappu Kumar; Kumar, Rahul
Spectrum sensing (SS) is one of the crucial functions of cognitive radio networks (CRNs). It decides whether the band or sub-band of the spectrum is available or not for secondary users (SUs). Energy detection (ED) is one of the very fundamental approaches of SS to detect whether primary users (PUs) are present or absent. It is mathematically intractable to derive closed-form expressions of composite multipath/shadowing for average probability of detection and average area under the receiver operating characteristic curve. In this paper, we have considered Nakagami-m/log-normal as composite fading with maximum ratio combining (MRC) diversity, and it is approximated by Gaussian-Hermite integration (G-HI). In addition, adaptive threshold or optimised threshold has been incorporated to overcome the problem of spectrum sensing at low signal-to-noise ratio (SNR). To verify the correctness of exact results and obtained analytical expression is collaborated with Monte Carlo simulations.